Physical activity can attenuate, but not eliminate, the negative relationships of high TV viewing with some chronic diseases: findings from a cohort of 60 202 Brazilian adults. (28th November 2019) - Werneck, André O; Oyeyemi, Adewale L; Collings, Paul J; Cyrino, Edilson S; Ronque, Enio R V; Szwarcwald, Célia L; Sardinha, Luís B; Silva, Danilo R P
Abstract: Background: This study examined the joint associations of leisure time physical activity and television (TV) viewing time with the prevalence of chronic diseases among Brazilian adults. Methods: Data from the Brazilian Health Survey, a nationally representative survey conducted in 2013 ( n = 60 202; ≥18 years), were used. Time spent in TV viewing and leisure physical activity, physician diagnoses of diabetes, hypertension and heart disease and information on co-variables (chronological age, education, ethnicity, candies/sweets consumption, sodium intake and tobacco smoking) were collected via interview. Descriptive statistics (mean and 95% confidence interval) and logistic regression models were used for etiological analyses. Results: Physical activity attenuated but did not eliminate the risk associated with high TV viewing for at least one chronic disease in the general population [odds ratio [OR]: 1.29 (1.11–1.50)] and among women [OR: 1.31 (1.09–1.60)], adults [OR: 1.24 (1.05–1.46)] and older adults [OR: 1.63 (1.05–2.53)]. On the other hand, physical activity eliminated the risk associated with high TV viewing for at least one chronic disease among men [OR: 1.24 (0.98–1.58)]. Conclusions: We conclude that physical activity can attenuate but not eliminate the negative effects of high TV viewing on chronic disease among subgroups of Brazilian adults.